2023
DOI: 10.1021/acssuschemeng.2c05753
|View full text |Cite
|
Sign up to set email alerts
|

Mussel-Inspired Electro-oxidation-Modified Three-Dimensional Printed Carriers for a Versatile Enzyme Immobilization Approach

Abstract: Conventional enzyme immobilization approaches can only immobilize certain specific enzymes with poor generality. Attempts to improve the universality of enzyme types tend to impart them with more enzymatic catalysis applications. Here, inspired by mussel adhesive proteins, we present a novel eco-friendly surface carrier that was 3D printed and modified by electro-oxidation for enzyme immobilization. The carrier was fabricated through 3D printing by transforming acrylonitrile butadiene styrene (ABS) material in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…It was found that the highest DH and enzyme loading (405.56 ± 0.46 mg/g) were obtained with an Alcalase/resin ratio of 0.9, which was 10 times higher than the immobilized enzyme loading (37.7 mg/g galV ) prepared by Tan et al [ 39 ]. The enzyme loading significantly decreased with additional Alcalase, as excessive Alcalase would lead to a spatial blockage between enzyme molecules [ 40 , 41 ]. Therefore, the Alcalase/resin ratio of 0.9 was chosen for subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that the highest DH and enzyme loading (405.56 ± 0.46 mg/g) were obtained with an Alcalase/resin ratio of 0.9, which was 10 times higher than the immobilized enzyme loading (37.7 mg/g galV ) prepared by Tan et al [ 39 ]. The enzyme loading significantly decreased with additional Alcalase, as excessive Alcalase would lead to a spatial blockage between enzyme molecules [ 40 , 41 ]. Therefore, the Alcalase/resin ratio of 0.9 was chosen for subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%